EFEK INJEKSI UDARA DAN STEAM TERHADAP KUALITAS SYNGAS HASIL GASIFIKASI SEKAM PADI MENGGUNAKAN FIXED–BED GASIFIER - Masfuri, Imron; Rahardjo, Bambang Suwondo (Jurnal Energi dan Lingkungan (Enerlink), 2009)
Biomass gasification is more benefit compared to direct combustion because ofmore flexibility gas product that can be directed use as combusted gas in gasengine power generation or chemical feedstocks as well as synthetic fuelbelongs to added market value. Since 2007, PT National Champignon (PTNatcham) in Wonosobo ? Central Java have been operating 1 (one) unit of fixed?bed updraft gasifier by rice?husk fuel feeding using air as gasification agent forit?s mushroom plant electricity needs through gas engine 400 kW. Fluctuation ofgasifictaion temperature in each of gasifier zones is affected by injectionpressures of air+steam, as well as opening valves of air and steam. The optimumsteam injection can only be carried?out at opening valve of steam 50% and airof 7/19 (volumetric ratio of steam/air = 0.6?0.7) with bottom temperatur ofgasifier, Tbottom = 650oC at pressure condition of 4,5 bar. Syngas with H2/COratio of 1,26? 1,71 have sufficient met the requirements of syngas quality forsynthesis process of Fischer?Tropsch to be processed futhermore for syntheticfuel producing.Kata kunci: sekam padi, gasifikasi, gas sintetis, Gas?To?Liquid, Fischer?Tropsch